The effect of visual-graphic tooth brushing teaching method on the plaque index of 8-year old pupils of Epifanio Delos Santos Elementary School - Correa, Maria Katrina Rosario O.
INTRODUCTION: Statistics show that 87.4% of the entire Philippine population and 75.7% of twelve-year-old Filipino children suffer from dental caries (NMEDS, 2011). This oral health condition in the country is alarming considering that dental caries is a preventable disease. Studies have shown the effectiveness of tooth brushing in caries reduction and plaque reduction (Okada et al, 2000) (Srivastava et al, 2013). It is therefore important that the proper tooth brushing technique be taught to children who are still in their formative years. This study aims to determine the effect of Visual-Graphic tooth brushing teaching method on the plaque indices of 8-year-old school children.